Human alpha-L-iduronidase: cDNA isolation and expression. - Scott, H S (1991)
alpha-L-Iduronidase (IDUA; EC 3.2.1.76) is a lysosomal hydrolase in the metabolic pathway responsible for the degradation of the glycosaminoglycans heparan sulfate and dermatan sulfate. A deficiency of IDUA in humans leads to the accumulation of these glycosaminoglycans and results in the lysosomal storage disorder mucopolysaccharidosis type I. We have isolated and sequenced cDNA clones containing part of the human IDUA coding region and used PCR from reverse-transcribed RNA to obtain the full IDUA sequence. Analysis of the predicted 653-amino acid precursor protein shows that IDUA has a 26-amino acid signal peptide that is cleaved immediately prior to the amino terminus of the 74-kDa polypeptide present in human liver IDUA. The protein sequence contains six potential N-glycosylation sites. Northern blot analysis with IDUA cDNA detected only a single 2.3-kilobase mRNA species in human placental RNA; however, PCR analysis of fibroblast, liver, kidney, and placental RNA showed the existence of alternatively spliced mRNA from the IDUA gene. Southern blot analysis failed to detect major deletions or gene rearrangements in any of the 40 mucopolysaccharidosis type I patients studied. Expression of a full-length IDUA cDNA construct in Chinese hamster ovary cells produced human IDUA protein at a level 13-fold higher than, and with a specific activity comparable to, IDUA present in normal human fibroblasts.